Enhanced stabilization of aerosol-OT surfactant monolayer upon interaction with small amounts of bovine serum albumin at the air-water interface - Caetano, W.; Ferreira, M.; Oliveira, O. N.; Itri, R. (Elsevier B.V., 2004)
An investigation is made of the influence from small amounts of the protein bovine serum albumin (BSA) on the lateral organization of low molecular weight surfactant sodium bis-2-ethylhexyl sulfosuccinate (AOT) at the air-water interface. Surface pressure (pi - A), surface potential (DeltaV - A) and Brewster angle microscopy (BAM) experiments were carried out, with particular emphasis on the monolayer stability under successive compression-expansion cycles. AOT monolayer is not stable at the air-water interface, which means that the majority of AOT molecules go into the aqueous subphase as monomers and/or normal micelles. When a waiting time elapses between spreading and compression, the surfactant monolayer tends to reorganize partially at the air-water interface, with a monolayer expansion being observed for waiting times as large as 12 h. The incorporation of very small amount of BSA (10(-9) M) at the interface, also inferred from BAM, increases the monolayer stability as revealed by pi - A and DeltaV - A results. For a waiting time of circa 3 h, the mixed monolayer reaches its maximum stability. This must be related to protein (and/or protein-surfactant complexes) adsorbed onto the AOT monolayer, thus altering the BSA conformation to accommodate its hydrophobic/hydrophilic residues. Furthermore, the effects from such small amounts of BSA in the monolayer formation and stabilization mean that the AOT monolayer responds cooperatively to BSA. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: langmuir monolayer; aerosol-OT; bovine serum albumin; surfactant-protein interaction; stability